VertCalc: hydraulic software to sharp-crested weir design and flow measurement - Ribeiro, Thales Augusto (2020)
Sharp-crested weir are simple, inexpensive, and useful hydraulic structures for measuring flow in open channels. Although obtaining the flow rate when the dimensions of the weir are known is easy, the inverse problem is more complex: designing a weir for a maximum expected flow as it is necessary to solve an 3/2 and 5/2 degree equation, which cannot be performed analytically and requires the use of computational resources. This paper aimed to present the VertCalc, which is a free and offline software that has functions of estimating flow and design of weirs with rectangular (with or without contractions), triangular, and trapezoidal geometries, and make it available to the academic community and hydraulic professionals. The program was developed in the Visual Basic language and presented itself as easy to use and with reliable results when compared with the technical literature. The error analysis in estimating the values of the developed program resulted in percentages between 0.0% and 6.6%.